Exploring the Diverse Landscape of Layered Double Hydroxide-Based Nanomaterials - Coogan, Áine Fiona (Trinity College Dublin. School of Chemistry. Discipline of Chemistry, 2024)
This thesis details the synthesis, characterisation, and an exploration of the diverse application landscape of layered double hydroxide (LDH)-based nanomaterials. The aim is to showcase the potential of LDHs in chirality induction, advanced separation processes, photocatalysis, and luminescent sensing platforms, primarily focusing on environmental applications in line with the UN Sustainable Development Goals. The first project of this thesis involves the synthesis of CuAl-CO3 LDH nanosheets via aqueous co-precipitation, and an investigation of various routes of chirality induction in this material. The exploration of two distinct methods of chirality induction using chiral molecules led to the decomposition of the LDH phase, and subsequent formation of chiral CuO nanosheet clusters, with intense visible range chiroptical activity. The second study focuses on the development of new LDH/BNOx nanocomposites for advanced nanofiltration and photocatalysis. A combination of co-precipitation, liquid-phase exfoliation and vacuum filtration techniques were employed to produce membranes which exhibited exceptional performance for the retention of organic dyes - prevalent pollutants stemming from the textiles industry. These membranes also demonstrated photocatalytic degradation of dyes under visible-light conditions, acting as an innovative route to addressing concerns of membrane fouling. The third and final investigation explores lanthanide doping of LDHs, and their use as luminescent sensing platforms for environmental applications. Aqueous co-precipitation was used to produce Eu3+ and Tb3+-doped MgAl and ZnAl LDHs, which were employed for successful luminescent 'turn-off' sensing of dichromate in water. This work offers valuable insights into the quenching mechanism, detection limits, and economic viability of these materials, serving as a significant contribution to the field of environmental nanosensing. This results stemming from this thesis not only highlight the diversity of LDH-based nanomaterials for numerous applications through compositional variation, but also contribute to the further understanding of chiral nanostructures, advanced nanofiltration membranes, and sensing processes.
APPROVED
Keywords: Nanomaterials; 2D materials; Chirality; Photocatalysis; Environmental chemistry; Luminescent nanomaterials